2000
DOI: 10.1029/2000jb900134
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of water and argon permeability in natural clay‐bearing fault gouge under high pressure at 20°C

Abstract: Abstract. Quantification of fluid transport through fault zones is critical for the understanding of fault mechanics and prediction of subsurface fluid flow. The permeability of clay-bearing fault gouge has been determined using first argon then water as pore fluids under total confining pressures ranging up to 200 MPa and pore pressures of 40 MPa at room temperature. Use of the two pore fluids allows interactions between the gouge and pore fluids to be examined. Natural clay-bearing fault gouge recovered from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
155
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 182 publications
(168 citation statements)
references
References 31 publications
12
155
1
Order By: Relevance
“…Their measurements through graphitic mica-schist also indicate a similar degree of anisotropy at similar pressures and confirm that strong anisotropy persists within the mica-schist to greater pressures (27% anisotropy at 200 MPa). Measurements of fault rock permeability from numerous localities along the Carboneras fault have shown a remarkable degree of consistency, implying homogeneity of the fault rock in this region [Faulkner and Rutter, 1998, 2000, 2001. Velocities measured in the laboratory for the Carboneras fault zone have also previously been compared to those measured in field seismic surveys by Taylor et al [2015], with good agreement at pressures of about 2 MPa (corresponding to depths of approximately 80 m).…”
Section: 1002/2017gl073726mentioning
confidence: 87%
“…Their measurements through graphitic mica-schist also indicate a similar degree of anisotropy at similar pressures and confirm that strong anisotropy persists within the mica-schist to greater pressures (27% anisotropy at 200 MPa). Measurements of fault rock permeability from numerous localities along the Carboneras fault have shown a remarkable degree of consistency, implying homogeneity of the fault rock in this region [Faulkner and Rutter, 1998, 2000, 2001. Velocities measured in the laboratory for the Carboneras fault zone have also previously been compared to those measured in field seismic surveys by Taylor et al [2015], with good agreement at pressures of about 2 MPa (corresponding to depths of approximately 80 m).…”
Section: 1002/2017gl073726mentioning
confidence: 87%
“…We further note that the permeability measurements presented herein were measured using inert gas as the pore fluid. Permeability to water will likely be lower than the gas permeabilities provided herein due to the presence of swelling clays (although we note that only 5-6% of the clays are smectite) (Davy et al 2007;Faulkner and Rutter 2000;Shimamoto 2006, 2009). The relationship between permeability and clay content may also be more pronounced if water was used as the pore fluid.…”
Section: Matrix Permeability Of the Buntsandsteinmentioning
confidence: 99%
“…The basement thrust coincides with the convergence of the frontal thrust and the LSB reflector and thus appears to be disrupting the local lithostratigraphy ( Figure 5), suggesting that this feature causes the plate boundary to be located on the frictionally stronger frontal thrust. Because it has been suggested that rupture propagation in shallow accretionary prisms is facilitated by weak, clay-rich sediment [Faulkner et al, 2011] or high-overall pore pressures , the high-friction, well-drained deposits on the frontal thrust make the toe of the Kumano transect less conducive for earthquake propagation than adjacent areas (e.g., Muroto). This is supported by earlier experiments documenting that friction coefficients on the frontal thrust are $0.1 higher than on the Muroto decollement [Ikari and Saffer, 2011].…”
Section: Implications Of Basement Thrusting For Fault Behaviormentioning
confidence: 99%
“…However, our results show that the pelagic clay is also frictionally weak in general (consistently the second-weakest sample) and therefore is the next likely candidate to host the decollement if fluid pressure becomes further elevated relative to Unit V. Although sand-rich lithologies in Unit V exhibit high permeability and could act as fluid conduits [H€ upers and Kopf, 2012], the transition zone is located $25-35 km from the trench so that the path length of fluid escape is large, a condition favorable for maintaining overpressure. Additionally, shearing of sediment can significantly reduce fault-perpendicular permeability [e.g., Brown and Moore, 1993;Faulkner and Rutter, 2000;Kopf, 2001;Ikari and Saffer, 2012], so it is possible that permeability reduction driven by shearing in Unit V could limit vertical flow in Unit VI and build overpressure. Since the strengths of the volcaniclastic and pelagic samples are very similar, only a small amount of pore pressure increase may be necessary for further decollement step-down.…”
Section: Transition Zonementioning
confidence: 99%